The Intertemporal Influence Of The Global Trade War And The Rupiah Exchange Rate On Exports And Imports In Indonesia From An Islamic Economic Perspective In 2013-2024 - Setya Ayu Nastiti; Dimas Pratomo; Gustika Nurmalia (Nuban Jagadhita Centre, 2026)
Purpose: This study aims to analyze the intertemporal impact of the global trade war and fluctuations in the rupiah exchange rate on Indonesia's export and import performance from an Islamic economic perspective during the period 2013–2024. The trade war between the United States and China since 2018 has created international trade uncertainty and changes in tariff policies that affect developing countries, including Indonesia. In addition, changes in the rupiah exchange rate against the United States dollar also affect export competitiveness and national import expenditure. Methodology: This study uses a quantitative method with an exploratory approach and annual time series analysis for 2013–2024. Secondary data were obtained from the Indonesian Central Bureau of Statistics, the Ministry of Trade of the Republic of Indonesia, and other official institutions, then analyzed using time series regression to determine the partial and simultaneous effects of independent variables on Indonesian trade. Findings: The results of this study are expected to provide empirical evidence regarding the influence of the global trade war and exchange rates on Indonesia's exports and imports and their compliance with Islamic economic principles, such as justice (al-'adl), balance (tawazun), and benefit (maslahah). The novelty of this research lies in the simultaneous integration of global trade war analysis and the rupiah exchange rate from an Islamic economic perspective, which has rarely been studied in previous research. This is an open-access article under the CC BY-SA license.